2019
DOI: 10.12982/cmujns.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Outcomes of Affordable Custom Wheelchair Seating for an Individual with Cerebral Palsy: Case Report

Abstract: The person with cerebral palsy has a range of functional limitations which can restrict activities of daily living. Sitting for extended periods is a pertinent issue to address. Custom seating orthosis combined with a wheelchair could reduce issues associated with long-term sitting in this population. The custom seating system for a child with cerebral palsy GMFCS Level IV was provided and outcome measures which measured functional grasping and seat pressure distribution was evaluated while the patient was sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…This is in line with previous studies by various researchers who have been actively searching for the most suitable choice of ASO for CP patients (Angsupaisal et al, 2017;Chung et al, 2008;Polhan et al, 2019;Ries, Novacheck & Schwartz, 2014;Ryan, 2016;Sahinoglu, Coskun & Bek, 2017;Vekerdy, 2007). The seating orthosis developed by Polhan et al (2019) and Sahinoglu et al (2017) are shown in Figure 1 Based on an interview with parents regarding the seating and engagement of CP patients, Bolas and Boyle (2017) found that using the autonomous mobility and level of social skills of ASO patients is considered meaningful if they can be sociable, learn new skills, be self-sufficient, have fun, and achieve personal objectives. Therefore, Bolas and Boyle indicated that when evaluating the best for CP patients and their families, it is important to figure out what is relevant and important outcomes.…”
Section: Adaptive Seating Orthosis (Aso)supporting
confidence: 91%
“…This is in line with previous studies by various researchers who have been actively searching for the most suitable choice of ASO for CP patients (Angsupaisal et al, 2017;Chung et al, 2008;Polhan et al, 2019;Ries, Novacheck & Schwartz, 2014;Ryan, 2016;Sahinoglu, Coskun & Bek, 2017;Vekerdy, 2007). The seating orthosis developed by Polhan et al (2019) and Sahinoglu et al (2017) are shown in Figure 1 Based on an interview with parents regarding the seating and engagement of CP patients, Bolas and Boyle (2017) found that using the autonomous mobility and level of social skills of ASO patients is considered meaningful if they can be sociable, learn new skills, be self-sufficient, have fun, and achieve personal objectives. Therefore, Bolas and Boyle indicated that when evaluating the best for CP patients and their families, it is important to figure out what is relevant and important outcomes.…”
Section: Adaptive Seating Orthosis (Aso)supporting
confidence: 91%